Moderation Effects of Ownership Concentration on The Relationship between Cost Stickiness and Enterprise Risk of Indonesian Listed Agricultural Companies - Aprilcilla, Aprilcilla (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
This paper examined the relationship between the cost stickiness and enterprise risk, and further studied the moderation effects of the ownership concentration on the above relationship. This study used 4 control variables, there are firm size, leverage, profitability and capital intensity. The focus of this study is agricultural companies that listed on the Indonesia Stock Exchange in the period of 2013-2018 as the research sample. Data analysis used a multivariate regression analysis model, where multiple linear regression analysis is used to test the first hypothesis and moderated regression analysis (MRA) to test the second hypothesis. The results of multivariate regression analysis show that both hypotheses are rejected. Cost stickiness does not affect enterprise risk and ownership concentration also does not moderate the relationship of cost stickiness to enterprise risk.